INTERNATIONAL CONTROL IN FIGHT AGAINST DOPING IN SPORTS - Elena A, Barabanova; Lenara R, Klimovskaya; Revol M, Valeev (Gênero & Direito, 2019)
This article explores the mechanisms of international control in the field of fight against doping. International legal control is one of the means of ensuring the fulfillment by the states of their obligations and is important in achieving the effectiveness of the implementation of legal norms. The paper analyzes the relevant provisions of two international legal acts that constitute the legal basis in anti-doping activities: The Anti-Doping Convention of the Council of Europe and the International Convention against Doping in Sport. In accordance with the provisions of international legal acts, special monitoring bodies are established to monitor the implementation by the states of their obligations through online questionnaires. The focus is on the activities of these specialized agencies. At the same time, the nature of international legal control is not limited only to checking the behavior of states, but also is expressed in the prevention of violations of the international law. In this regard, it is needed an element that establishes the responsibility of states for failure to fulfill their international obligations. Such a mechanism would be the document Operational Guidelines and System of Consequences for Non-Compliance with the Regulations Adopted as Annex to the International Convention against Doping in Sport